The Effect Of Workload And Work-Life Balance On Female Employee Performance At Bank Jatim Gresik Branch - Revaldo, Muhammad Tapus; Kustini, Kustini (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine and analyze the influence of workload and work-life balance on employee performance at Bank Jatim Gresik Branch. In this context, workload and work-life balance are considered important in achieving optimal performance within a company. This research is a quantitative study, and the method used is a survey method, with a questionnaire as the data collection tool. The population in this study consists of female employees at Bank Jatim Gresik Branch, totaling 50 respondents, using a saturated sampling technique. Data analysis was conducted using Partial Least Squares (PLS). The results of this study indicate that workload and work-life balance have a positive effect on employee performance.